Optimasi unjuk kerja pada sistem pendinginan adsorpsi dengan siklus pemanasan-ulang kombinasi - I Gusti Agung Bagus Wirajati; Putu Wijaya Sunu; Ida Ayu Gede Bintang Madrini; Ni Kadek Muliati (Jurnal Teknosains, 2022)
The adsorption refrigeration system is a cooling system that offers several benefits, including being environmentally friendly due to the very small amount of global warming effect given, the lack of potential for ozone depletion, the low energy consumption of its operation, the low heat source used in its operation and good for reducing gas emissions on earth. This paper describes a combined reheating adsorption refrigeration system with three heat exchangers, as well as operating modes. The operation of the adsorption refrigeration system with combined reheating is schematically described with operational modes and diagrams. This adsorption cooling system is made up of three heat exchangers (H), one evaporator, and one condenser. The combination cycle is intended for heat exchanger systems that operate in a reheat cycle (H1 and H2) and a non-reheating cycle (H3). This paper also discusses system cycle time optimization. Research to get the optimum value of cycle time in this system is still rarely done and therefore optimization of cycle time is carried out on the system to get the best performance. The PSO (particle swarm optimization) program is paired with the MATLAB program to simulate the performance of the system under discussion while also enhancing its performance. The goal of this work is to use simulation to determine the optimal system performance versus the overall cycle time, which includes adsorption/desorption time, pre-cooling and pre-heating time as well as mass recovery time. Getting the best value for the entire cycle time is made possible by fusing the simulation of the system's process performance with performance optimization. As a results, the greatest increase in the optimization results' performance value occurs at a heat source temperature of 55ºC with a longer time to achieve optimal performance.